Digital Diplomacy in The Era of Fragmentation: Indonesia's Strategy to Keep Pace with Global Financial Hegemony Through Regional Payment Connectivity - Rachmi Amalia (International Journal Labs, 2026)
This study analyzes the transformation of the Interstate Quick Response Code Indonesia Standard (QRIS) and the Local Currency Transaction (LCT) scheme as instruments in Indonesia's digital finance strategy, how QRIS-LCT plays a role as a means of structural resistance to the dominance of the US Dollar and Western payment systems (Visa/Mastercard), and its contribution in strengthening Indonesia's Digital Sovereignty and Financial Autonomy in the Southeast Asian region. Using the framework of International Political Economy, specifically the concept of Structural Power, this study proves that the integration of payments in ASEAN and expansion into East Asia is a manifestation of Digital Neomercantilism. This study applies a qualitative descriptive approach. Data collection is carried out through literature review and document analysis, utilizing secondary information from academic journals, official government reports (such as Bank Indonesia), credible media, and relevant international cooperation documents. The results of the study until 2025 show that the Interstate QRIS, supported by LCT, has been successfully implemented in ASEAN countries (Thailand, Malaysia, Singapore, the Philippines, and Vietnam) and has expanded to East Asia (Japan, Korea, China). These efforts serve as a significant dedollarization tool and strengthen regional macroeconomic independence. An important finding that was revealed was the geopolitical reaction from the United States (through the USTR), which showed that QRIS was considered a threat to the dominance of the existing global financial system. Nonetheless, there are still operational challenges that need to be addressed, such as imbalances in transaction volumes and digital literacy levels that must be improved